The Role of Productive Waqf and Management Strategies Towards the Welfare of the Indonesian Community - Umu Syaidah; Bambang Suyadi (Institut Studi Islam Muhammadiyah Pacitan, 2026)
Waqf is a portable or income-generating asset given for public (Islamic) benefit as a gift. The law of waqf in Islam is considered sunnah muakkadah, which is a highly recommended sunnah due to its extraordinary virtue and widespread benefits for the community. This research was completed using a qualitative descriptive research method with a literature study. Literature study is an activity of taking and collecting data from books, previous research journals, and trusted websites, then reading, recording, and reprocessing them. The results of this study show that the management of productive waqf can be seen in the waqf land in West Java which is rented out for agricultural land, where the results finance education and health programs, create jobs, and improve food security. Strategies that can be used are (1) long-term productive allocation in properties (MRT, commuter trains), agriculture, trade, and industry (2) investment in youth education for global human resources (3) digital literacy of waqf for millennials and Gen-Z as well as (4) consumptive assistance for the poor and persons with disabilities. The implementation of this strategy not only increases the number of waqif and waqf funds, but also accelerates the growth of the productive economy.